The memoirs of Ceija Stojka child survivor of the Romani Holocaust - Stojka, Ceija 1933-2013 (Women and gender in German studies, 2022)
First English translation of the memoirs of Austrian Romani Holocaust survivor, writer, visual artist, musician, and activist Ceija Stojka (1933-2013), along with poems, an interview, historical photos, and reproductions of her artworks